(untitled) (Journal of the Sociology and Theory of Religion, 2017)
Despite the small number of its faithful, the Ahmadiyya faith stands out for the public presence and political support that it achieves in the West, this is due to some of its characteristics - such as the defense of religious freedom or the firm condemnation of terrorism - that make from this Islamic sect a dreamed Islam; This article investigates its origins and message, to know to what extent this Islam dreamed in reality is.